Implementation of Key Performance Indicator (KPI) System, Absence and Organizational Culture on Employee Perfor-mance at PT. Prima Husada Cipta Medan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of the implementation of the Key Performance Indicator (KPI) system, absenteeism, and organizational culture on employee performance at PT Prima Husada Cipta Medan. The background of the study is based on the suboptimal employee performance as indicated by the continued discrepancy in the achievement of performance indicators, a relatively high level of absenteeism in certain periods, and the uneven internalization of organizational culture. This study uses a quantitative approach with a causal associative method. Data were obtained by distributing questionnaires to 135 employees determined using the Slovin formula. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that the partial implementation of the KPI system, absence, and organizational culture have a positive and significant effect on employee performance. Simultaneously, these three independent variables also have a significant effect on employee performance. These findings indicate that effective KPI implementation, disciplined absence management, and consistent strengthening of organizational culture can improve employee performance. This research is expected to be a consideration for management in improving human resource management in a sustainable manner.